The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1152/ajplung.00013.2012
|View full text |Cite
|
Sign up to set email alerts
|

Titanium oxide nanoparticle instillation induces inflammation and inhibits lung development in mice

Abstract: Nanoparticles are used in an increasing number of biomedical, industrial, and food applications, but their safety profiles in developing organisms, including the human fetus and infant, have not been evaluated. Titanium oxide (TiO(2)) nanoparticles, which are commonly used in cosmetics, sunscreens, paints, and food, have been shown to induce emphysema and lung inflammation in adult mice. We hypothesized that exposure of newborn mice to TiO(2) would induce lung inflammation and inhibit lung development. C57BL/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 45 publications
1
22
1
Order By: Relevance
“…Nanoparticles are present in cosmetics, paint, sunscreens, and food (287). Using titanium oxide nanoparticles (average diameter 8 -10 nm), Ambalavanan and coworkers (22) reported that exposure of mouse pups at P4 to single or multiple doses of nanoparticles provoked an increase in the expression of proinflammatory mediators and blunted lung development (assessed at P14; by MLI and RAC). In a related study, Chan and coworkers (60) described the muted expression of Cyp1A1, a cytochrome P-450 superfamily member, in neonatal, but not adult rats, after exposure to ultrafine particular matter, which is a key component of vehicle exhaust.…”
Section: New Mediators and Modulators Of Impaired Alveolarizationmentioning
confidence: 99%
“…Nanoparticles are present in cosmetics, paint, sunscreens, and food (287). Using titanium oxide nanoparticles (average diameter 8 -10 nm), Ambalavanan and coworkers (22) reported that exposure of mouse pups at P4 to single or multiple doses of nanoparticles provoked an increase in the expression of proinflammatory mediators and blunted lung development (assessed at P14; by MLI and RAC). In a related study, Chan and coworkers (60) described the muted expression of Cyp1A1, a cytochrome P-450 superfamily member, in neonatal, but not adult rats, after exposure to ultrafine particular matter, which is a key component of vehicle exhaust.…”
Section: New Mediators and Modulators Of Impaired Alveolarizationmentioning
confidence: 99%
“…Although various toxicities of nano-TiO 2 have been studied with different cell and animal models, [20][21][22][23][24] the research on their possible impacts on the cardiovascular system is relatively limited, especially the underlying toxicological mechanisms remain unclear. 2,25 Thus, it is meaningful to deeply study the effects of nano-TiO 2 on the cardiovascular system and the underlying biological mechanisms, which will in turn provide scientific data for the risk assessment and developing novel strategies to mitigate their toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficients of tissue are shown in the table [2]. It was defined as grams (wet weight of tissue/body weight).…”
Section: Coefficients Of Tissuementioning
confidence: 99%
“…Titanium dioxide nanoparticles (TiO 2 NP), which generally utilized in prettifying, paints, sunscreens, and nutrition, induced emphysema and lung sore in mice (2). TiO 2 particles are not immunologically active and may be an essential supplement in beat normal gut cell hypo-responsiveness to endogenous luminal molecules.…”
Section: Introductionmentioning
confidence: 99%